2021
DOI: 10.1039/d1cc04826k
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an isoquinolinone framework from carboxylic-ester-directed umpolung ring opening of methylenecyclopropanes

Abstract: An unprecedented reaction pattern of functionalized methylenecyclopropanes (MCPs) has been disclosed in this paper, in which the nucleophilic attack of anionic species onto partially polarity-reversed MCP unit can be realized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Extending the reaction time to 5 hours could not afford a better result, and 1 a is fully consumed upon generating 3 a‐OH in 57% yield along with unknown side products (Table 1, entry 7). As reported in our previous work, a higher temperature promoted the nucleophilic attack on the MCP group [6] . However, in this cascade cyclization reaction, the intermolecular Michael addition might be incompatible with the increased temperature, resulting in the moderate yields.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…Extending the reaction time to 5 hours could not afford a better result, and 1 a is fully consumed upon generating 3 a‐OH in 57% yield along with unknown side products (Table 1, entry 7). As reported in our previous work, a higher temperature promoted the nucleophilic attack on the MCP group [6] . However, in this cascade cyclization reaction, the intermolecular Michael addition might be incompatible with the increased temperature, resulting in the moderate yields.…”
Section: Methodssupporting
confidence: 54%
“…We inferred that increasing the amount of 1 a would reduce the influence of ambient moisture or water in the reaction system, providing the more reliable results since a large amount of EtMgBr was employed in the reaction. As we expected, when 0.5 mmol of 1 a was applied in the reaction, the yields of 3 a-OH could be obviously improved at various temperatures (37% for room temperature, 58% for 50 °C, and 60% for 70 °C, respectively) upon shorter reaction time (Table 1, entries [4][5][6]. Extending the reaction time to 5 hours could not afford a better result, and 1 a is fully consumed upon generating 3 a-OH in 57% yield along with unknown side products (Table 1, entry 7).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…A variety of compounds reacting with methylenecyclopropanes, either in the addition reaction on the ternary ring or in the addition reaction on the double bond, can be used to selectively synthesize many of the target products . Wei et al reported a ring–opening reaction between carboxylate and methylenecyclopropanes to construct isoquinolinone skeletons . Li and co-workers proposed a palladium-catalyzed hydroalkylation of methylenecyclopropanes using a simple hydrazone as a carbanion equivalent through highly selective carbon–carbon σ-bond breaking under mild conditions .…”
Section: Introductionmentioning
confidence: 99%
“…16 Wei et al reported a ring−opening reaction between carboxylate and methylenecyclopropanes to construct isoquinolinone skeletons. 17 Li and co-workers proposed a palladium-catalyzed hydroalkylation of methylenecyclopropanes using a simple hydrazone as a carbanion equivalent through highly selective carbon−carbon σ-bond breaking under mild conditions. 18 Xu's group reported a method to form strained spiro [2,3] hexane with high enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%